The Anti-Inflammatory Effect of Pistacia Lentiscus in a Rat Model of Colitis - Ostovan M; Fazljou SMB; Khazraei H; Araj Khodaei M; Torbati M (Dove Medical Press, 2020)
Maryam Ostovan,1 Seyyed Mohammad Bagher Fazljou,1 Hajar Khazraei,2 Mostafa Araj Khodaei,1,3 Mohammadli Torbati4 1Department of Persian Medicine, School of Traditional Medicine, Tabriz University of Medical Sciences, Tabriz, Iran; 2Colorectal Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 3Aging Research Institute, Tabriz University of Medical Sciences, Tabriz, Iran; 4Department of Traditional Pharmacy, School of Traditional medicine, Tabriz University of Medical Sciences, Tabriz, IranCorrespondence: Hajar Khazraei Email Khazraee@sums.ac.irIntroduction: The mastic tree (Pistacia lentiscus), belonging to the Anacardiaceae family, has anti-inflammatory and antioxidant properties. This study aims to assay the anti-inflammatory effects of mastic in rats with colitis.Methods: Forty-eight male Sprague-Dawley rats were randomly divided into six groups of control, colitis without treatment, colitis with mastic (400 mg/kg/daily) administered orally or intra-rectally, colitis with prednisolone (5 mg/kg of body weight), and colitis with sesame oil for seven successive days. Treatment effects were evaluated by determining cytokines (TNFα, IL6) and myeloperoxidase (MPO) activity, macroscopic scores, and histopathological parameters. The results of each group are compared with colitis without treatment group.Results: After administering sesame oil, the MPO level was reduced significantly compared to colitis without the treatment group (P=0.025). The mastic oil (400 mg/kg orally) administration was effective in reducing colitis severity through the reduction in the total colitis index (p=0.046) after 7 days. The Intra-rectal administration of mastic decreased TNF-α significantly, similar to prednisolone and control groups compared to the colitis without treatment group (p=0.024). The IL-6 did not change in the mastic and sesame oil groups.Conclusion: According to our results, mastic and sesame oil have anti-inflammatory properties, suggesting that they could be used as natural sources to lessen the ulcerative colitis inflammation.Keywords: mastic, colitis, inflammation, rats, sesame